2009
DOI: 10.1161/circulationaha.108.824730
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoexcitation by Oxidative Stress in the Brain Mediates Arterial Pressure Elevation in Obesity-Induced Hypertension

Abstract: Background-Obesity is one of the major risk factors for cardiovascular disease and is often associated with increased oxidative stress and sympathoexcitation. We have already suggested that increased oxidative stress in the brain modulates the sympathetic regulation of arterial pressure in salt-sensitive hypertension, which is often associated with obesity. The present study was performed to determine whether oxidative stress could mediate central sympathoexcitation in the initial stage of obesity-induced hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 59 publications
5
93
1
2
Order By: Relevance
“…We evaluated the responses of renal sympathetic nerve activity (RSNA) and arterial pressure to acute intracerebroventricular (ICV) administration of an antioxidant agent, Tempol, and the level of ROS in the hypothalamus. In our previous reports, [17][18][19] we showed the effects of acute ICV Tempol but did not show the effects of chronic ICV Tempol. Thus, our previous data only suggested a pathophysiological role of brain ROS but did not show the usefulness of central antioxidant treatment.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…We evaluated the responses of renal sympathetic nerve activity (RSNA) and arterial pressure to acute intracerebroventricular (ICV) administration of an antioxidant agent, Tempol, and the level of ROS in the hypothalamus. In our previous reports, [17][18][19] we showed the effects of acute ICV Tempol but did not show the effects of chronic ICV Tempol. Thus, our previous data only suggested a pathophysiological role of brain ROS but did not show the usefulness of central antioxidant treatment.…”
mentioning
confidence: 64%
“…We have also shown that increased oxidative stress in the brain elevated arterial pressure, possibly through central sympathoexcitation, in a salt-sensitive hypertension model, Dahl salt-sensitive rats, 18 and in an obesity-induced hypertension model, high-fat diet-fed rats, 19 in both of which systemic ROS overproduction has been reported. 20,21 Similarly, increased oxidative stress has also been reported in CKD.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…44 A depressor effect was induced by intravenous administration of hexamethonium hydrochloride (30 mg kg À1 ). The maximal decrease in the MAP was considered as an index of sympathetic activity.…”
Section: Measurement Of Plasma Nementioning
confidence: 99%